Long-Term Outcome of Esophageal Anastomosis - Rintala, R. J.; Pakarinen, M. P. (European Journal of Pediatric Surgery, 2013)
After repair of esophageal atresia (EA) in a newborn, esophageal dysmotility presenting as dysphagia and symptomatic gastroesophageal reflux are common. Significant esophageal morbidity associated with EA extends into adulthood. In adulthood approximately one-fifth of the patients have developed epithelial metaplastic changes, one-third of these have intestinal metaplasia (Barrett esophagus). Surgical complications, increasing age, and impaired esophageal motility predict the development of epithelial metaplasia after repair of EA. To date, worldwide, eight cases of esophageal cancer have been reported in young adults treated for EA. Incidence of esophageal cancer after EA repair is very much likely to increase in the future. Life-long endoscopic follow-up is warranted in patients with EA.
Keywords: esophageal atresia; long-term outcomes